The PENGARUH DAYA TARIK WISATA, LOKASI, DAN FASILITAS TERHADAP KEPUTUSAN BERKUNJUNG PADA WISATAWAN DI PANTAI GANDORIAH KOTA PARIAMAN: The Effect of Tourist Attractions on Visitors' Decisions to Visit Gandoriah Beach in Pariaman City - Syukrial, Syukrial; Hendri, Novi; Putri, Revalni Eka (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2025)
This study aims to determine the influence of tourist attractions, location, and facilities on tourists' visiting decisions at Gandoriah Beach, Pariaman City. The purpose of this study was to partially and simultaneously test the influence of tourist attractions, location, and facilities on tourists' visiting decisions at Gandoriah Beach, Pariaman City. This study used a quantitative method with a sample size of 100 people. The data analysis technique used was multiple linear regression analysis. The research instrument tests used were validity and reliability tests. The classical assumption tests used were data normality tests, linearity tests, multicollinearity tests, and heteroscedasticity tests. Meanwhile, for hypothesis testing, the T test and F test were used. The analysis tool used was regression with the help of SPSS version 26 for Windows. The results of the study show that the tourist attraction variable has a significant influence on the decision to visit tourists at Gandoriah Beach, Pariaman City through calculations with a t-value of 5.170 which is greater than the t-table, namely 1.66023 (5.170 > 1.66023) with a significance rate of 0.000 meaning less than 0.05 (0.000 <0.05). The location variable has a significant effect on the decision to visit tourists at Gandoriah Beach, Pariaman City. This is evidenced by the t-count value of 4.305 which is greater than the t-table of 1.66023 (4.305 > 1.66023) with a significance rate of 0.000 meaning less than 0.05 (0.000 <0.05). The facility variable has a significant effect on the decision to visit tourists at Gandoriah Beach, Pariaman City. This is evidenced by the t-count value of 5.662 which is greater than the t-table of 1.66023 (5.662 > 1.66023) with a significance rate of 0.000 meaning less than 0.05 (0.000 <0.05). The variables of tourist attraction, location, and facilities have a significant influence on the decision to visit tourists at Gandoriah Beach, Pariaman City, through calculations with an Fcount value of 44.190> Ftable 2.70 with sig = 0.000 <0.05. The Ftable value can be seen in the F distribution table, in column 3 (Df = k-1, Df = 4-1 = 3) and row 97 (Df2 = n-k, Df2 = 100-3 = 97), where the Ftable value = 2.70. The joint contribution is 56.7% to the dependent variable of the decision to visit (Y) while the rest is influenced by other variables not examined in this study.